Ontologies supporting the process of selection and evaluation of COTS software components - Konys, Agnieszka (Ontologie wspomagające proces doboru i oceny składnikówoprogramowania COTS, 2011)
The general aim of this paper is to present ontologies supporting COTS components selection and evaluation process. The general statements of an ontology project and construction were presented as well. Thus the whole steps of the ontology construction processfor COTS were described in details. The exemplary parts of ontologies for methods and techniques, information tools and frameworks, methods and tools for ontology evaluation and COTS ERP software components were presented. Moreover, the formal way of COTS ontology description was provided. The conclusions finish this paper
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2011, Nr 206, s. 81-95
Keywords: ontology; COTS software; COTS selection and evaluation; COTS components; COTS methodology; ontologia; oprogramowanie COTS; wybór i ocena COTS; składniki COTS; metodologia COTS